Environmental Microbiota Drives Microbial Succession and Metabolic Profiles during Chinese Liquor Fermentation - Wang, Xueshan; Du, Hai; Zhang, Yan; Xu, Yan (Applied and environmental microbiology, 2018)
Many microorganisms in the environment participate in the fermentation process of Chinese liquor. However, it is unknown to what extent the environmental microbiota influences fermentation. In this study, high-throughput sequencing combined with multiphasic metabolite target analysis was applied to study the microbial succession and metabolism changes during Chinese liquor fermentation from two environments (old and new workshops). SourceTracker was applied to evaluate the contribution of environmental microbiota to fermentation. Results showed that Daqu contributed 9.10 to 27.39% of bacterial communities and 61.06 to 80.00% of fungal communities to fermentation, whereas environments (outdoor ground, indoor ground, tools, and other unknown environments) contributed 62.61 to 90.90% of bacterial communities and 20.00 to 38.94% of fungal communities to fermentation. In the old workshop, six bacterial genera ( Lactobacillus [11.73% average relative abundance], Bacillus [20.78%], Pseudomonas [6.13%], Kroppenstedtia [10.99%], Weissella [16.64%], and Pantoea [3.40%]) and five fungal genera ( Pichia [55.10%], Candida [1.47%], Aspergillus [10.66%], Saccharomycopsis [22.11%], and Wickerhamomyces [3.35%]) were abundant at the beginning of fermentation. However, in the new workshop, the change of environmental microbiota decreased the abundances of Bacillus (5.74%), Weissella (6.64%), Pichia (33.91%), Aspergillus (7.08%), and Wickerhamomyces (0.12%), and increased the abundances of Pseudomonas (17.04%), Kroppenstedtia (13.31%), Pantoea (11.41%), Acinetobacter (3.02%), Candida (16.47%), and Kazachstania (1.31%). Meanwhile, in the new workshop, the changes of microbial community resulted in the increase of acetic acid, lactic acid, malic acid, and ethyl acetate, and the decrease of ethyl lactate during fermentation. This study showed that the environmental microbiota was an important source of fermentation microbiota and could drive both microbial succession and metabolic profiles during liquor fermentation. IMPORTANCE Traditional solid-state fermentation of foods and beverages is mainly carried out by complex microbial communities from raw materials, starters, and the processing environments. However, it is still unclear how the environmental microbiota influences the quality of fermented foods and beverages, especially for Chinese liquors. In this study, we utilized high-throughput sequencing, microbial source tracking, and multiphasic metabolite target analysis to analyze the origins of microbiota and the metabolic profiles during liquor fermentation. This study contributes to a deeper understanding of the role of environmental microbiota during fermentation.